2019
DOI: 10.1111/liv.14125
|View full text |Cite
|
Sign up to set email alerts
|

Relations of liver fat with prevalent and incident chronic kidney disease in the Framingham Heart Study: A secondary analysis

Abstract: Background & Aims:Prior studies demonstrated an association between non-alcoholic fatty liver disease and chronic kidney disease (CKD), though data are conflicting.We examined the association between liver fat and prevalent and incident CKD in the Framingham Heart Study (FHS). Methods:We included FHS participants who underwent computed tomography (CT) from 2002 to 2005 (n = 1315). After excluding heavy alcohol use (n = 211) and missing covariates (n = 117), the final sample included 987 participants. For the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
3
23
0
1
Order By: Relevance
“…either by abnormal levels of serum liver enzymes or by imaging techniques) is significantly associated with an increased incidence of CKD [34][35][36][37][38][39][40][41][42][43][44][45][46] (Table 1). Notably, in most of these studies the significant association between NAFLD and increased incidence of CKD persisted even after adjustment for age, sex, obesity, hypertension, T2DM and other potential confounding factors.…”
Section: Nafld Ckdmentioning
confidence: 99%
“…either by abnormal levels of serum liver enzymes or by imaging techniques) is significantly associated with an increased incidence of CKD [34][35][36][37][38][39][40][41][42][43][44][45][46] (Table 1). Notably, in most of these studies the significant association between NAFLD and increased incidence of CKD persisted even after adjustment for age, sex, obesity, hypertension, T2DM and other potential confounding factors.…”
Section: Nafld Ckdmentioning
confidence: 99%
“…Hence, the identification of further independent predictors for CKD is crucial in clinical practice. At present, there is strong evidence linking NAFLD and CKD, indicating that patients with NAFLD could need more intensive surveillance and treatment in order to reduce their risk of developing CKD [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Additionally, accumulating data also suggest the existence of an association between PNPLA3 rs738409 gene variant (which is strongly linked to the development of NAFLD and its advanced forms) and risk of CKD [23][24][25][26][27][28][29], thereby suggesting that PNPLA3 may directly influence the kidney injury [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the last 5-10 years, several observational reports have documented that imaging-diagnosed NAFLD is independently associated with an increased risk of developing CKD in patients with and without T2DM [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In addition, accumulating evidence now suggests that the rs738409 G allele is associated with lower values of estimated glomerular filtration rate (eGFR) as well as with a higher risk of CKD in adults but also in adolescents and children, even after adjustment for the presence of NAFLD and multiple CKD risk factors [13,[24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between nonalcoholic fatty liver disease (NAFLD) and chronic kidney disease (CKD) has attracted much attention, since they share similar risk factors and pathogenic mechanisms, such as insulin resistance (IR), diabetes mellitus (DM), hyperlipidemia and obesity [12][13][14][15][16][17][18]. While numbers of previous studies indicated the presence and severity of NAFLD was a potential contributory risk factor for the development and progression of CKD, recent studies suggested no adverse association between NAFLD hepatic steatosis and renal function both in general populations and diabetic individuals [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%